Screening for familial hypercholesterolaemia in childhood: Avon Longitudinal Study of Parents and Children (ALSPAC). (May 2017) - Futema, Marta; Cooper, Jackie A.; Charakida, Marietta; Boustred, Christopher; Sattar, Naveed; Deanfield, John; Lawlor, Debbie A.; Timpson, Nicholas J.; Humphries, Steve E.; Hingorani, Aroon D.; ,
Abstract: Background and aims: Familial hypercholesterolaemia (FH) is an autosomal-dominant disease with frequency of 1/500 to 1/250 that leads to premature coronary heart disease. New approaches to identify FH mutation-carriers early are needed to prevent premature cardiac deaths. In a cross-sectional study of the Avon Longitudinal Study of Parents and Children (ALSPAC), we evaluated the biochemical thresholds for FH screening in childhood, and modelled a two-stage biochemical and sequencing screening strategy for FH detection. Methods: From 5083 ALSPAC children with cholesterol measurement at age nine years, FH genetic diagnosis was performed in 1512 individuals, using whole-genome or targeted sequencing of known FH-causing genes. Detection rate (DR) and false-positive rate (FPR) for proposed screening thresholds (total-cholesterol > 1.53, or LDL-C > 1.84 multiples of the median (MoM)) were assessed. Results: Six of 1512 sequenced individuals had an FH-causing mutation of whom five had LDL-C > 1.84 MoM, giving a verification-bias corrected DR of 62.5% (95% CI: 25–92), with a FPR of 0.2% (95% CI: 0.1–0.4). The DR for the TC cut-point of 1.53 MoM was 25% (95% CI: 3.2–65.1) with a FPR of 0.4% (95% CI: 0.2–0.6). We estimated 13 of an expected 20 FH mutation carriers (and 13 of the 20 parental carriers) could be detected for every 10, 000 children screened, with false-positives reliably excluded by addition of a next generation sequencing step in biochemical screen-positive samples. Conclusions: Proposed cholesterol thresholds for childhood FH screening were less accurate than previously estimated. A sequential strategy of biochemical screening followed by targeted sequencing of FH genes in screen-positive children may help mitigate the higher than previously estimated FPR and reduce wasted screening of unaffected parents. Highlights: 6 FH mutations were found in ALSPAC children cohort by next generation sequencing. Proposed children LDL cut-offs resulted in higher than expected false positive rate. Sequencing step could improve the efficiency of parental FH screening.